Pertumbuhan Vegetatif dan Kadar Gula Biji Jagung Manis (Zea mays saccharata, Sturt) di Pekanbaru - Surtinah Surtinah; Seprita Lidar (Jurnal Ilmiah Pertanian, 2017)
Research conducted an experiment using a completely randomized design environment with four replications, and the design of treatment used is six varieties of sweet corn. Analysis of data using polynomial regression, the parameters measured were plant height, leaf number, leaf length, leaf width, and sugar beans, followed by analyzing the relationship between the growth of plants with a sugar content of sweet corn kernels. The results showed that leaf width gives a weak relationship to the sugar content of sweet corn seed, and leaf length, number of leaves and plant height had a close relationship to the sugar content of sweet corn kernels.